Perceptions on support, challenges and needs among parents and caregivers of children with developmental disabilities in Croatia, North Macedonia and Serbia: a cross-sectional study - Jelena Međaković; Antonia Čivljak; Tatjana Zorčec; Vesna Vučić; Danijela Ristić-Medić; Aleksandra Veselinović; Marta Čivljak; Livia Puljak (BMC, 2024)
Abstract Background Parents/caregivers of children with developmental disabilities (CDD) have a wide range of support needs and there are various interventions available. Support, challenges, and needs among parents/caregivers of CDD likely vary in different geographical settings. This study aimed to analyze the perceptions of support, challenges, and needs among parents/caregivers of CDD in Croatia, North Macedonia, and Serbia. Methods We conducted a cross-sectional study in March-April 2023 within the Erasmus + SynergyEd project. The eligible participants were parents and caregivers of CDD in Croatia, North Macedonia, and Serbia, who filled out a modified Caregiver Needs Survey online. Results Among 953 participants, 542 (57%) were from Croatia, 205 (21%) were from North Macedonia and 206 (22%) were from Serbia. The most common diagnosis of participants' children was autism spectrum disorder (26%). The child most often received the first diagnosis at the median of 2 years, diagnosed by a team of professionals. More than half (58%) of children attended preschool and public school, while 22% did not attend any schooling. Additional support from the state/city/county was received by 66% of CDD. Most participants declared not participating in association/organization for family support. Participants mostly (68%) used experts who work with the child as a source of information about their child's condition, followed by the Internet (53%). In the last 12 months, 60% of participants had difficulties with the availability of services in their area or problems getting appointments. The biggest problem in getting support was ensuring the child's basic rights were protected. Participants stated that ensuring greater rights for CDD was the greatest need for their families. Conclusion Parents/caregivers of CDD in Croatia, North Macedonia, and Serbia faced multiple challenges, but most of them were satisfied with the services provided to their children. Future efforts to develop policies and services related to CDD should consider the opinions of their parents/caregivers and disparities in access to services.